Surto de toxoplasmose humana em Santa Maria: revisão sistemática, genotipagem de isolados humanos, e soroprevalência de gatos domésticos - Fernandes, Fagner D'ambroso (2024)
Toxoplasmosis is a disease that affects a variety of hosts, including humans, with a potential impact on One Health. In 2018, in Santa Maria, RS, 902 human cases of toxoplasmosis were confirmed, characterizing the largest outbreak described worldwide to date. In chapter 1, the genotypic characterization of human isolates of Toxoplasma gondii, obtained during the toxoplasmosis outbreak in Santa Maria, was described using Restriction Fragment Length Polymorphism (RFLP) techniques and Sanger sequencing, showing that this sequencing can be a tool for future genotypic characterizations of this parasite. the determination of the seroprevalence of domestic cats infected by T. gondii after the human toxoplasmosis outbreak in Santa Maria, RS, was carried out. For the evaluation of seroprevalence, samples from domestic cats in Santa Maria, attended at the Veterinary University Hospital of the Federal University of Santa Maria (HVU-UFSM), were subjected to the Indirect Immunofluorescence Reaction (IFAT) technique for the detection of anti-T. gondii IgG antibodies. In chapter 3, a bibliographic review of the human toxoplasmosis outbreak in the municipality of Santa Maria was conducted. For this purpose, all notification reports of positive human cases for toxoplasmosis, published by the Municipal Government of Santa Maria, were described, enabling the understanding of the evolution of cases in the municipality. In addition, all scientific studies published up to the moment (time of publication of the scientific article), involving samples from the toxoplasmosis outbreak in Santa Maria; aspects related to the control and prevention of new infections during the outbreak; perspectives and post-outbreak resolutions related to public policies and monitoring of the parasite in water samples for human consumption were described. The presentation of these three chapters can contribute to elucidating the largest outbreak of human toxoplasmosis in Santa Maria, RS, providing important information for aspects related to One Health.